La gestión tecnológica del trámite documentario y la satisfacción del usuario en el gobierno local - Yasuda Aguilar, Enzo Giancarlo (2024)
This study proposes to identify the relationship between the technological management of document processing and the satisfaction of users who access this channel of attention in the public sector. The methodology used is basic, non-experimental with cross-sectional, quantitative approach, the level of study is correlational and the hypothetical-deductive method was used. Likewise, the technique used was the survey and the instrument used was the questionnaire. Cronbach's alpha was used to determine the reliability of the instrument, and a very high reliability value was obtained. In this sense, the results showed the existence of a significant relationship between the study variables, with a Spearman's Rho correlation coefficient of 0.599, that is, moderately positive. This is due to the fact that the local government adequately applies technology management in the processing of documents, and this satisfies the users. Finally, it is concluded that there is a relationship between technology management and user satisfaction in local government.